Binder-free hydrogenated NiO–CoO hybrid electrodes for high performance supercapacitors. Issue 40 (7th April 2015) - Yang, Mingyang; Lv, Fucong; Wang, Zhenyu; Xiong, Yiqiu; Li, Minchan; Wang, Wenxi; Zhang, Lihua; Wu, Sisi; Liu, Hongtao; Gu, Yingying; Lu, Zhouguang
Abstract : Three-dimensional bind-free hydrogenated NiO–CoO hybrid electrodes were prepared and exhibited superior electrochemical performance for supercapacitors. Abstract : Binder-free NiO–CoO hybrid electrodes were directly grown on nickel foam by electrodeposition and subsequent annealing in 5% H2 /95% N2 gas at 300 °C. Crystal structure, elemental analysis, surface morphology and chemical compositions of the composites were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) equipped with an energy dispersive X-ray analysis system. The hydrogenated NiO–CoO hybrid electrodes were evaluated as electrodes for supercapacitors which demonstrated promising electrochemical performance with high specific capacitance, excellent rate capability, and stable cycling.